The Leverage Factor: Credit Cycles and Asset Returns - Davis, Josh; Taylor, Alan M. (Management Science, 2022)
Research has found strong links between past credit booms and adverse outcomes for macroeconomic aggregates like output and investment. However, are price impacts also seen more widely in broad asset classes such as equity and fixed-income markets? We document such a robust and significant connection using a large sample of historical data for many advanced countries since 1870. Credit boom periods with a high “leverage factor” tend to be predictably followed by unusually low returns to risky equities, in absolute terms and relative to a safe fixed-income portfolio. Fixed income is a safe haven at these times and has slightly higher than normal returns. We show these properties hold in-sample and out-of-sample. Return predictability because of the leverage factor is distinct from that because of momentum (lagged return) and value (cashflow relative to price). Trading strategies built on the leverage factor accrue meaningful excess profits out-of-sample. This paper was accepted by Victoria Ivashina, finance.